Revisitação do lendário amazônico através da escritura dramática - Pozzetti, Gislaine Regina (2013)
The spontaneity and freedom that the legends hold are fundamental elements to the do theatrical. Thus, the legend is revisited in this dissertation, placing it in dialogue with the dramaturgy, seeking in the reworking of the narratives to evidence the presentification, characteristic of both theater and legend. For this, a reflection is developed about the meaning of the legendary and its relationship with the daily lives of individuals, specifically those who inhabit the Amazon. In another direction, it also seeks to stimulate discussion different theories about the concepts, structures and forms used by the dramaturgy from the classics to the post-drama, in order to expand the possibilities creative for the text that has the legend as thematic, providing another space for enunciation for the legendary. In application terms, the dissertation presents reflections developed from the practical experience of building four dramatic texts.